Concept vs Notion and Lexical Meaning: What is the Difference? - Khairullina, Dinara (Journal of History Culture and Art Research, 2018)
This paper analyzes a series of terms – “concept”, “notion”, “meaning”, which are closely related to each other and constantly interact in modern linguistics. The applicability of this work is apparent, since its matter is characterized by a certain terminological ambiguity. Distinction of these terms is necessary to ascertain their roles in the acquisition, comprehension and expression of knowledge about the real world. The article reviews the main theoretic issues of cognitive and cultural linguistics and reviews the Russian and foreign literature on the subject of the study. Researchers observe both unifying and distinctive characteristics of these concepts. The author’s opinion is that “lexical meaning”, “notion” and “concept” are different terms. They are interrelated, but not equivalent. It seems reasonable that they belong to similar categories of thinking but are taken in different systems of relationships. The article is addressed to linguists, lecturers of linguistic disciplines, postgraduates and students of relevant specialties.